Symmetric Solutions of Nonlinear Fractional Integral Equations via a New Fixed Point Theorem under FG-Contractive Condition. (10th September 2019) - Kumar Nashine, Hemant; Ibrahim, Rabha W.
Abstract: We set up the existence of a symmetric outcome of a system of simultaneous nonlinear fractional integral equations, that arises in motion of water wave on smooth surface, with the help of a common fixed point theorem satisfying a generalized FG -contractive condition. To accomplish this, we introduce first the concept of generalized FG -contractive condition for two pairs of self-mappings in a complete metric space and then we establish requisites for common fixed point results for weakly compatible mappings followed by a suitable example.